Les femmes dans l'aviation: Assurer des emplois de qualité et favoriser le recrutement et le maintien en poste - David Seligson (Organisation internationale du Travail (OIT), 2024)
This paper includes information on some of the current issues faced by women in civil aviation. Through a sectoral gender lens, it examines employment, women's career cycles and the main decent work opportunities and challenges in the sector. It also identifies ways of accelerating the achievement of gender equality. Progress for women in the world of work has been slow in a number of sectors, including in civil aviation, where there are clear gender gaps in a range of occupations. The rapid expansion of the sector provides an opportunity for a transformative and proactive agenda for gender equality. Yet, a series of challenges need to be addressed if the future of women in civil aviation is not to simply replicate the discriminatory patterns of the past. This working paper is a first step towards exploring some of these challenges and identifies opportunities for the future of decent and sustainable work in the aviation industry. The paper is the result of an unprecedented combination of industry and worker inputs, and it has benefitted from information and data provided by the International Civil Aviation Organization. Governments, workers, employers and international organizations all have an important role to play in establishing, promoting and implementing policy choices that advance gender equality. These choices will depend on changing contexts, as gender equality is a constantly moving target.
Keywords: 330; Aviation professions; women; employment history; career planning; gender equality; airline; Luftverkehrsberufe; Frauen; Erwerbsverlauf; Karriereplanung; Gleichberechtigung; Fluggesellschaft; Welt